EVALUASI PROGRAM BANTUAN STIMULAN PERUMAHAN SWADAYA (BSPS) BAGI MASYARAKAT BERPENGHASILAN RENDAH DI KELURAHAN OESAPA KECAMATAN KELAPA LIMA KOTA KUPANG - Maria Nofrini Burga; Jacoba D. Niga; Mariayani O. Rene; Adriana R. Fallo (Journal Education and Government Wiyata, 2025)
This research is motivated by the high number of uninhabitable houses (RTLH) in Kupang City, one of which is in Oesapa, which is one of the villages in Kupang City. Therefore, there is a need for a programme called the self-help housing stimulant assistance programme (BSPS) which is a housing assistance programme for people who have a low-income background who have not yet obtained a livable house. The purpose of this study was to determine and describe the implementation of the BSPS programme for low-income communities in Oesapa Village, Kelapa Lima Sub-district, Kupang City using William N. Dunn's (2003) evaluation criteria of effectiveness, equity and accuracy. This research uses a qualitative approach with a descriptive research type. Data were collected through observation, interview and documentation techniques and analysed using the miles and Huberman model. Research results showed that the self-help housing stimulant assistance (BSPS) programme in Kelurahan Oesapa is considered less than optimal because the beneficiaries do not implement the programme in accordance with the objectives of the programme, namely doing self-help. BSPS programme has not been fully equitable for low-income communities and the delivery of information has not been fully equitable for low-income communities. for low-income people and the delivery of information has also not been evenly delivered. information has also not been delivered evenly